The Influence of Financial Literacy and Entrepreneurial Orientation on the Performance of MSMEs in Indonesia with Business Innovation as a Mediating Variable - Qosim, Nanang (Westscience Press, 2025)
This study investigates the influence of financial literacy and entrepreneurial orientation on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with business innovation acting as a mediating variable. A quantitative research design was employed, using data collected from 200 MSME owners and managers across diverse sectors through structured questionnaires based on a 5-point Likert scale. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3.0). The results reveal that both financial literacy and entrepreneurial orientation have a positive and significant effect on MSME performance. Furthermore, business innovation significantly mediates the relationship between the two independent variables and business performance. These findings underscore the importance of financial capability, strategic entrepreneurial behavior, and innovation adoption in enhancing MSME sustainability and competitiveness. The study provides practical recommendations for policymakers and business development stakeholders to support integrated capacity-building efforts for MSMEs in Indonesia.